North Korea’s Nuclear Weapons Development: The Impact for International Security and Stability - Adiningsih, Aprilia Putri; Nte, Ngboawaji Daniel (International Law Discourse in Southeast Asia, 2022)
The development of nuclear weapons today is in many cases one of the threats of future wars. In fact, the development of this weapon is considered to be able to disrupt international stability and security. Nuclear weapons have developed since World War II, which destroyed Hiroshima and Nagasaki in 1945. Until now, several countries are still competing to develop nuclear weapons. Nuclear weapons are weapons that get power from nuclear reactions and have tremendous destructive power, a nuclear bomb can destroy a city. Countries that have nuclear weapons include the United States, Russia, Britain, France, China, India, North Korea, and Pakistan. Nuclear weapons can become weapons of mass destruction which of course threaten the stability of international security. As one of the nuclear-armed countries, North Korea is modernizing the country by focusing its strength on the planning economy, heavy industry, and military development. This study aims to analyze the development of North Korea's nuclear weapons in the context of international stability and security and its impact on international law enforcement, especially in the region of Southeast Asian countries.